Adsorption study of methyl orange by chitosan/polyvinyl alcohol/zeolite electrospun composite nanofibrous membrane - Habiba, Umma; Siddique, Tawsif A.; Lee, Jacky Jia Li; Tan, Chin Joo; Ang, Bee Chin; Afifi, Amalina Muhammad (Elsevier, 2018)
The chitosan/polyvinyl Alcohol/zeolite electrospun composite nanofibrous membrane was fabricated for adsorption of methyl orange. The EDX, TGA and tensile test were carried out for the characterization of the membrane. The Young's Modulus of the nanofibrous membranes increased by more than 100% with the addition of zeolite to chitosan/PVA. The batch adsorption tests were conducted by varying the initial concentration of methyl orange, contact time and pH of the dye solution. UV–vis results showed that most of the dye was adsorbed within 6 min. An adsorption kinetic study was carried out using the pseudo-second-order kinetic model, Lagergren-first-order model and intra particle diffusion model. The adsorption kinetics obeyed the Pseudo second order model. The adsorption mechanism was analyzed using the Langmuir and Freundlich isotherm model. The experimental data fits well with the Freundlich model. The adsorption capacity of the membrane was 153 mg/g. Adsorption capacity was decreased with increasing pH value. The resulting nanofiber became less active over methyl orange after several runs.